2023
DOI: 10.1002/aenm.202302643
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Internal Stress‐Induced Micro‐Short Circuit Events in Sulfide‐Based All‐Solid‐State Li‐Metal Batteries via Operando Pressure Measurements

Jiabao Gu,
Xiaoxuan Chen,
Zhifeng He
et al.

Abstract: Despite the relatively low stiffness of sulfide solid‐state electrolytes (SSEs), which makes them capable of better formability and accommodation for volume changes of active materials, the low fracture toughness (KIC) indicates a high susceptibility to fracture caused by electrochemo‐mechanical stresses. This susceptibility to mechanical damages and the subsequent lithium filament penetration, manifesting as micro‐short circuit events, seriously hinders the practical application of lithium metal in high‐energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…As shown in Figure 5c,d, the gc-LSB 0.025 S pellets have a denser surface, indicating that the Bi 3+ doping is effective in reducing interfacial and grain boundary impedance, benefiting the Li + transportation. 60,61 In addition, the comparison of EDS elemental mapping between gc-LSB 0.025 S and gc-LSS (Figures S5 and S6) also confirms the successful doping of Bi 3+ and the uniform distribution of Sn, S, and Bi in the electrolyte.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…As shown in Figure 5c,d, the gc-LSB 0.025 S pellets have a denser surface, indicating that the Bi 3+ doping is effective in reducing interfacial and grain boundary impedance, benefiting the Li + transportation. 60,61 In addition, the comparison of EDS elemental mapping between gc-LSB 0.025 S and gc-LSS (Figures S5 and S6) also confirms the successful doping of Bi 3+ and the uniform distribution of Sn, S, and Bi in the electrolyte.…”
Section: Resultsmentioning
confidence: 53%
“…Based on the analysis of electrolyte powders in Figure a,c, it can be observed that gc-LSS and gc-LSB 0.025 S, which are both submicrometer materials with agglomerates, exhibit no significant difference from one another. As shown in Figure c,d, the gc-LSB 0.025 S pellets have a denser surface, indicating that the Bi 3+ doping is effective in reducing interfacial and grain boundary impedance, benefiting the Li + transportation. , In addition, the comparison of EDS elemental mapping between gc-LSB 0.025 S and gc-LSS (Figures S5 and S6) also confirms the successful doping of Bi 3+ and the uniform distribution of Sn, S, and Bi in the electrolyte.…”
Section: Resultsmentioning
confidence: 66%
“…Lithium plating results in LLI and may make the cell less safe since it can induce internal short circuits by allowing lithium dendrites to form [17]. Various modeling techniques of lithium plating have been presented in [50][51][52][53]. Lithium plating can be estimated using the Butler-Volmer equation [47].…”
Section: Lithium Platingmentioning
confidence: 99%
“…Furthermore, mechanical stress could permit the electrolyte to penetrate the anode material and start chemical reactions that eventually weaken the anode and reduce battery capacity [50]. Moreover, internal short circuits brought on by stress-induced dendritic formation-a process in which microscopic lithium metal fibers protrude from the anode surface-can enter the separator and result in safety hazards like thermal runaway, overheating, or even explosions [51][52][53]59]. As the particles go through a phase transition, the intercalation of lithium ions into the anode may cause sudden variations in volume [60,61].…”
Section: Stressmentioning
confidence: 99%